General approach to medium-sized ring ethers via hydrolytic and oxidative kinetic resolutions: stereoselective syntheses of (-)-cis-lauthisan and (+)-isolaurepan - Tripathi, Divya; Pandey, Satyendra Kumar; Kumar, Pradeep (Tetrahedron, 2009)
A short and enantioselective approach to medium ring ethers and its application to the syntheses of (-)-cis-lauthisan and (+)-isolaurepan are described. The synthetic strategy features Jacobson's Hydrolytic Kinetic Resolution (HKR), oxidative resolution of secondary alcohol, and highly diastereoselective Et(3)SiH/TMSOTf-promoted reductive cyclization of a hydroxy ketone to give exclusively the different medium-sized cis-disubstituted cyclic ethers. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: cis-Reductive cyclization; Jacobson's Hydrolytic Kinetic Resolution (HKR); Oxepanes; Oxidative resolution of secondary alcohol; Ring ether

General and concise asymmetric synthesis of sphingosine, safingol and phytosphingosines via tethered aminohydroxylation - Kumar, Pradeep; Dubey, Abhishek; Puranik, Vedavati G. (Organic & Biomolecular Chemistry, 2010)
A novel, practical and efficient enantioselective synthesis of sphingoid bases, L-threo-[2S,3S]-sphinganine (safingol), L-threo-[2S,3S]-sphingosine, L-arabino-[2R,3S,4R] and L-xylo-[2R,3S,4S]-C(18)-phytosphingosine is described. The synthetic strategy features the Sharpless kinetic resolution and tethered aminohydroxylation (TA) as the key steps.

General and concise asymmetric synthesis of sphingosine, safingol and phytosphingosines via tethered aminohydroxylation (vol 8, pg 5074, 2010) - Kumar, Pradeep; Dubey, Abhishek; Puranik, Vedavati G. (Organic & Biomolecular Chemistry, 2020)